The Sole DNA Ligase in Entamoeba histolytica Is a High-Fidelity DNA Ligase Involved in DNA Damage Repair - Azuara-Liceaga, Elisa; Betanzos, Abigail; Cardona-Felix, Cesar S.; Castañeda-Ortiz, Elizabeth J.; Cárdenas, Helios; Cárdenas-Guerra, Rosa E.; Pastor-Palacios, Guillermo; García-Rivera, Guillermina; Hernández-Álvarez, David; Trasviña-Arenas, Carlos H.; Diaz-Quezada, Corina; Orozco, Esther; et al. (Frontiers in Cellular and Infection Microbiology, 2018)
The protozoan parasite Entamoeba histolytica is exposed to reactive oxygen and nitric oxide species that have the potential to damage its genome. E. histolytica harbors enzymes involved in DNA repair pathways like Base and Nucleotide Excision Repair. The majority of DNA repairs pathways converge in their final step in which a DNA ligase seals the DNA nicks. In contrast to other eukaryotes, the genome of E. histolytica encodes only one DNA ligase (EhDNAligI), suggesting that this ligase is involved in both DNA replication and DNA repair. Therefore, the aim of this work was to characterize EhDNAligI, its ligation fidelity and its ability to ligate opposite DNA mismatches and oxidative DNA lesions, and to study its expression changes and localization during and after recovery from UV and H2O2 treatment. We found that EhDNAligI is a high-fidelity DNA ligase on canonical substrates and is able to discriminate erroneous base-pairing opposite DNA lesions. EhDNAligI expression decreases dafter DNA damage induced by UV and H2O2 treatments, but it was upregulated during recovery time. Upon oxidative DNA damage, EhDNAligI relocates into the nucleus where it co-localizes with EhPCNA and the 8-oxoG adduct. The appearance and disappearance of 8-oxoG during and after both treatments suggest that DNA damaged was efficiently repaired because the mainly NER and BER components are expressed in this parasite and some of them were modulated after DNA insults. All these data disclose the relevance of EhDNAligI as a specialized and unique ligase in E. histolytica that may be involved in DNA repair of the 8-oxoG lesions.